Hegemoni Laki-Laki di Balik Keikutsertaan Mengerjakan Kerja Domestik dalam Iklan MotionLife 2024 - Hasan, Eka Bita Ghulam; Binarum, Fausta Raditya; Kengtyas, Gupita Prajwalita; Ananda, Dhimas Aryo Vipha (Universitas Muhammdiyah Yogyakarta, 2025)
The MotionLife 2024 insurance advertisement focuses on gender roles within the family, particularly in terms of household chores. The aim of this research is to investigate the representation of male hegemony in the advertisement, which shows conventional stereotypes about how men and women divide roles. The denotative, connotative, and inherent mythological meanings are discussed in the advertisement scenes using hegemony theory and a semiotic approach in this research. The research results show that men have significant responsibilities outside of household chores as family protectors, while women have household duties. This representation shows a highly patriarchal culture, where women are often considered subordinate in family decision-making. The results show that changes in gender representation in the media are crucial to supporting gender equality in society.